Analisis Sentiment Terhadap Diabetes Menggunakan Algoritma Naïve Bayes, Random Forest, SVM Pada Media Sosial X - Apriani, Linda; Hendrastuty, Nirwana (Building of Informatics, Technology and Science (BITS), 2025)
Diabetes is one of the chronic diseases that has received widespread attention in society, especially on social media X. This is due to the increasing number of sufferers every year. Based on data from the World Health Organization (WHO), in 2021 it is estimated that 537 million people aged 20-79 years are living with diabetes, an increase from the 2019 estimate of 463 million people. In addition, around 1.3 million deaths are caused by diabetes, with 4 percent of them occurring before the age of 70. This condition occurs due to high blood sugar levels that interfere with the body's metabolic functions, making it difficult for the body to process sugar optimally. This study aims to compare the performance of Naïve Bayes, Random Forest, and Support Vector Machine (SVM) algorithms in sentiment analysis related to diabetes. The research data was obtained from the Twitter platform with a total of 8,401 tweets collected using crawling techniques using certain keywords in the time span of 2024 to 2025. The data then went through a pre-processing stage to produce clean data. Tests were conducted to evaluate the accuracy of each model in predicting public sentiment. The test results show that the SVM algorithm provides the best performance with 85% accuracy, followed by Random Forest with 82% accuracy, and Naïve Bayes with 74% accuracy before the application of Synthetic Minority Oversampling Technique (SMOTE). After optimization using SMOTE, the SVM algorithm still showed the best performance with 96% accuracy, followed by Random Forest with 95% accuracy, and Naïve Bayes with 85% accuracy. Based on these results, SVM proved to be the most effective algorithm in classifying sentiment related to diabetes. It is hoped that the results of this research can contribute to efforts to manage diabetes through a better understanding of public perceptions.